The Development of the Intermediate SnO2–Sb2O5 Layer on Titanium Substrate for Oxygen Evolution Anodes in Seawater Electrolysis - Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2009)
An attempt is made to replace the use of IrO2 by SnO2–Sb2O5 in the intermediate layer which is necessary to avoid the growth of insulating titanium oxide on the titanium substrate for oxygen evolution γ-MnO2 type Mn1-x-yMoxSnyO2+x anodes in seawater electrolysis. The manganese–molybdenum–tin triple oxides, Mn1-x-yMoxSnyO2+x, prepared by anodic deposition on the SnO2–Sb2O5-coated titanium substrate from MnSO4, Na2MoO4 and SnCl4 solutions showed around 98.6% initial oxygen evolution efficiency at a current density of 1000 Am-2 in 0.5 M NaCl of pH 1 at room temperature. In order to increase the stability of the anodes, coating at various times to form the intermediate SnO2–Sb2O5 layer with sufficient thickness on titanium substrate, was performed. The Mn1-x-yMoxSnyO2+x electrodes deposited on the intermediate layer formed from seven times coating showed about 98% oxygen evolution efficiency after 20 h electrolysis. A small addition of Sb2O5 to the intermediate layer (that is, Sb5+/Sn4+ = 0.124 in the coating solution) seems to be more effective to replace the use of IrO2 for high electronic conductivity and activity of oxygen evolution in seawater electrolysis. The formation of the double oxides of the intermediate SnO2–Sb2O5 layer after seven times coating seemed responsible for both high conductivity and stability of the Mn1-x-yMoxSnyO2+x anodes. Keywords: CO2 recycling, oxygen evolution electrode, intermediate SnO2–Sb2O5 layer, seawater electrolysis, titanium substrate. DOI: 10.3126/jncs.v23i0.2097 J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page: 54-64